Analisis Efektivitas Pemanfaatan Laboratorium Kimia di Sekolah Menengah Atas Negeri di Kabupaten Lombok Timur - Rekasawiji, Spir Senyum; Hadisaputra, Saprizal; Junaidi, Eka (FKIP University of Mataram, 2025)
This study aims to determine the effectiveness of using chemical laboratory functions and tools in Public Senior High Schools throughout East Lombok Regency. The approach in this study uses a descriptive quantitative approach. The population of this study consisted of all high schools in East Lombok Regency. The sample for this study comprised six schools: SMAN 2 Selong, SMAN 3 Selong, SMAN 1 Terara, SMAN 1 Pringgabaya, SMAN 1 Sembalun, and SMAN 1 Labuhan Haji, which were selected using purposive sampling. Data collection used questionnaires and interviews; the questionnaire used was closed with a Likert scale. For the interpretation of problem data using the criteria of 5 categories (not effective, less effective, moderately effective, effective, very effective) which are determined by simple percentages and tables. Based on data analysis it is known that; 1) the effectiveness of the use of chemical laboratory functions in State Senior High Schools throughout East Lombok Regency has been effective (74.82%). 2) The effectiveness of the use of chemical laboratory equipment in State Senior High Schools throughout the East Lombok Regency has been effective (80.33%).